Flowers for Algernon - Keyes, Daniel (Harcourt Brace modern classic., 1987)
Charlie embarks on a compelling but dangerous journey from retardation to genius. Oscar-winning film Charly starring Cliff Robertson and Claire Bloom-a mentally challenged man receives an operation that turns him into a genius ... and introduces him to heartache. When we first meet Charlie he is about to embark on a compelling but dangerous journey from retardation to genius. He has only a vague understanding of what will happen, but he is aware that knowledge and the ability to write are of paramount importance. So he doesn't hesitate for a moment to cooperate in a radical experiment designed to increase his intelligence, the key - he hopes - to being valued as a human being and to being loved. Daniel Keyes's powerful and highly original story of a young man whose quest for intelligence and knowledge parallels that of Algernon (the mouse who is an earlier subject of a similar experiment) remains unique in imaginative literature. We follow Charlie Gordon's mental, emotional, and spiritual growth. We watch with excitement as he becomes the focus of attention by the scientific world, his intellectual capacities far surpassing those of the psychologists and neurosurgeons who engineered his metamorphosis. We also follow the progress of his romance with two women, one who knew him before the experiment as well as with another, who knows him only as the attractive, bright, and sympathetic man he has become. And, finally, we hope against hope that what happens suddenly, unexpectedly, to Algernon will not happen to Charlie.